Effectiveness of Sub-district KUAs in Premarital Guidance for Adolescents as an Effort to Prevent Underage Marriage in North Sulawesi Province - Suprijati Sarib; Youlanda (Fakultas Syariah Institut Agama Islam Negeri Palu, 2024)
The purpose of this research is to examine the effectiveness of KUA guidance for premarital age adolescents in North Sulawesi and the differences in understanding of adolescents who get Premarital guidance from KUA in North Sulawesi. This research is qualitative research, the type of research is field research. The data collection methods used are observation, interview, and documentation. The results showed that in terms of guidance for adolescents related to pre-marital knowledge, before guidance showed a percentage of 51.02% less understanding and after guidance showed a percentage of 57.14% understanding from a total of 98 adolescents. This shows that so far the guidance for adolescents related to pre-marital knowledge carried out by the Head of the KUA has been quite effective. Although the guidance has not been optimal, with the percentage difference from the teenagers who understand after the guidance is carried out.